Beyond Point-of-Care Ultrasound: Bedside Ultrasound in the Diagnosis of Soft Tissue Mass. Issue 2 (February 2020) - Scheier, Eric; Balla, Uri
Abstract : Abstract: Cancer is diagnosed in 1 in 7000 children annually. Here, we report 6 cases of a mass identified by the author, a novice sonographer in a pediatric emergency medicine fellowship, using point-of-care ultrasound, from January of 2017 to May of 2018. Identification of these cases early in presentation allowed for earlier involvement of the relevant specialist and shorter time to diagnosis and treatment, and might be expected to increase parent satisfaction as well.